UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN MELATI (Jasminum sambac) TERHADAP BAKTERI Propionibacterium acnes - ekaa kumalasari (Akademi Farmasi Mitra Sehat Mandiri Sidoarjo, 2022)
ABSTRACT Propionibacterium acnes is a gram-positive bacterium that can cause acne. One of the plant extracts that have the potential as antibacterial is jasmine leaf extract (Jasminum sambac). This study aimed to determine the antibacterial activity of jasmine leaf extract with concentrations of 20%, 40%, and 60% against Propionibacterium acnes bacteria. Jasmine leaves were extracted by maceration method using ethanol as solvent. The results of the extraction of jasmine leaves yield 7.25% (w/v). Based on the results of the phytochemical screening test, the thick extract of jasmine leaves showed the presence of flavonoid compounds, saponins, and tannins. The resulting jasmine leaf extract will be tested for antibacterial activity against Propionibacterium acnes with concentrations of 20%, 40%, and 60% using the disk diffusion method. The resulting inhibition zone will be measured with a caliper, a concentration of 20% has an average diameter of the smallest inhibition zone of mm, a concentration of 40% with a diameter of medium inhibition zone of 7.488 mm, and a concentration of 60% with the largest diameter of the inhibition zone. which is 9.872 mm. Based on the one way ANOVA test, a significance value of 0.000 was obtained which was less than 0.05 so that there were significant differences in the concentrations of 20%, 40%, and 60% of the inhibition zone of Propionibacterium acnes bacteria.